The Effectiveness of Restorative Justice in Resolving Juvenile Criminal Offenses in Indonesia - Erdin, Erwin; Shofiana, Afi; Indar, Indra Jaya (Hakim: Jurnal Ilmu Hukum dan Sosial, 2025)
The increasing number of juveniles encountering the legal system in Indonesia underscores the need for a more effective approach within the juvenile criminal justice system (SPPA). Restorative Justice (RJ) has been adopted as an alternative to the conventional punitive-oriented judicial system. However, the implementation of RJ in Indonesia continues to face several challenges, including a lack of understanding among law enforcement officers, limited rehabilitation facilities, and minimal victim participation in the resolution process. This study aims to analyze the effectiveness of RJ in resolving juvenile criminal offenses in Indonesia while identifying the challenges and strategies for improving its implementation. The research employs a normative and empirical legal approach, utilizing case studies of juvenile offenses resolved through RJ. Data is collected through interviews with law enforcement officials, victims, and offenders, as well as an analysis of relevant regulations, such as Law No. 11 of 2012 on the Juvenile Criminal Justice System. Findings reveal that over the past five years, the average success rate of RJ in resolving juvenile cases in Indonesia has reached 60%, with a 45% reduction in recidivism rates compared to the formal judicial system. However, obstacles such as inadequate legal training for law enforcement personnel and limited rehabilitation facilities remain significant challenges in RJ implementation. This study contributes to policy reform discussions on juvenile justice in Indonesia by recommending capacity-building initiatives for legal practitioners and strengthening victim engagement mechanisms in the RJ process. Additionally, it highlights the need for increased investment in rehabilitation infrastructure and further research into the application of RJ in addressing the rising cases of cyber-related offenses among juveniles